An unusual case of buried broken exodontia instrument in inferior alveolar canal - Mishra, Ravish; Yadav, Deepak; Kandel, Laxmi; Tripathi, Shashank; Singh, Sunil Kumar; Shubham, Snigdha; Dutta, Kishor (Journal of Chitwan Medical College, 2019)
Exodontia is a routine procedure in dental practice. Despite of adequate effort to perform the procedure with proper technique, some mishap may happen when defective or substandard instruments are used. This article reports a symptomatic case of lip paresthesia since 1 month who had undergone attempted surgical extraction of third molar in remote dental hospital. On examination there was presence of retained fractured third molar with exodontia instrument tip in inferior alveolar canal and is very uncommon surgical complications and not much reported in literatures. Patient was not aware of the condition till Orthopantomogram (OPG) was done which revealed presence of approximately 1.5 cm instrument tip in inferior alveolar canal. Third molar and instrument tip were successfully retrieved from canal under local anesthesia. Rarely, instruments breakage may occur during surgical procedures. It is the duty of every operating dental surgeon to check surgical instruments for signs of breakage and be prepared to solve a possible emergency. Retained fragments should be carefully studied prior to attempt of removal.